Long-term expression of rAAV2-hIL15 enhances immunoglobulin production and lymphokine-activated killer cell-mediated human glioblastoma cell death - YIANG, GIOU-TENG (D.A. Spandidos, 2013)
Glioblastoma is the most aggressive primary brain tumor and its prognosis remains poor despite different treatment modalities including surgery, radiotherapy and chemotherapy. Therefore, more useful treatments for glioblastoma patients are required. Human interleukin 15 (hIL15) is an immunomodulator that has antitumor activities. hIL15 combined with gene therapy method is also currently under cosideration as a treatment option. Since recombinant adeno-associated virus serotype 2 (rAAV2) with low immunogenicity and long-term gene expression in human clinical trials has been demonstrated, rAAV2 encoding hIL15 (rAAV2-hIL15) were used to inhibit human glioblastoma growth in the present study. rAAV2-hIL15, which is able to express IL15 protein with bioactivity, was successfully produced and purified. Data of this study demonstrated that the long-term expression of rAAV2-hIL15 enhances immunoglobulin (Ig) production and the cytotoxic activity of lymphokine-activated killer (LAK) cells. In addition, results of the present study showed that rAAV2-hIL15 delays tumor growth on a xenografted human glioblastoma mice model. Taken together, these results indicated that rAAV2-hIL15 constitutes a powerful and potent gene immunotherapy method for human glioblastoma treatment.